PENERAPAN METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR SDN 001 KUNTO DARUSSALAM - Yulizon Yulizon (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
Based on observations while on some teachers found the following symptoms: the teachers in these schools take advantage of the school environment as a learning resource only two to three times in one semester. Teachers are more frequently present lessons in the classroom despite the presented materials related to the school environment. From the interviews, most of the teachers admitted reluctantly invites students to learn outside the classroom, for reasons difficult to supervise. In addittion there are teachers who said that they could not and did not know in the use of the school environment as a learning resource. In accordance with the formulation of the problem, the purpose of this study was to determine whether the application method of giving task if the task granting application method to enhance capabilities utilizing teachers in the school environment as a learning resource in SDN 001 Kunto Darussalam. This type of research is action research school (PTS), which aims to determine the success of the implementation task giving methods to increase. Utilizing the ability of teachers in the school environment as a learning resource in SDN 001 Kunto Darussalam. This study consisted of two cycles, as for each cycle performed in two meetings. The stages are passed in classroom action research, planning/ preparatory actions, Implementation of the action, observation and reflection. From the description of data processing and discussion it was concluded that the ability of master in environmental utilizing the school as a learning resource obtained in the first cycle of 43% with a good category and the second cycle increased to 76% with very good category.